Discriminação e Nacionalidade - Sousa, Constança Urbano de (2015)
this short article discusses briefly the concepts of nationality, citizenship and the legal status of foreign citizens, at national and European level. Seeks to analyse the extent to which citizenship rights must be disconnected from the existence of the legal bond of nationality, in order to guarantee citizenship rights to all people based on the criterion of residence and not nationality.